Ultrasound Assessment of Diaphragm Thickness and Thickening: Reference Values and Limits of Normality When in a Seated Position - Boussuges, Alain; Rives, Sarah; Finance, Julie; Chaumet, Guillaume; Vallée, Nicolas; Risso, Jean-Jacques; Brégeon, Fabienne (Frontiers in Medicine, 2021)
Background: Diagnosing diaphragm dysfunction in the absence of complete paralysis remains difficult. The aim of the present study was to assess the normal values of the thickness and the inspiratory thickening of both hemidiaphragms as measured by ultrasonography in healthy volunteers while in a seated position. Methods: Healthy volunteers with a normal pulmonary function test were recruited. The diaphragmatic thickness was measured on both sides at the zone of apposition of the diaphragm to the rib cage during quiet breathing at end-expiration, end-inspiration, and after maximal inspiration. The thickening ratio, the thickening fraction, and the thickness at end-inspiration divided by the thickness at deep breathing were determined. The mean values and the lower and upper limits of normal were determined for men and women. Results: 200 healthy volunteers (100 men and 100 women) were included in the study. The statistical analysis revealed that women had a thinner hemidiaphragm than men on both sides and at the various breathing times studied. The lower limit of normality of the diaphragm thickness measured at end-expiration was estimated to be 1.3 mm in men and 1.1 mm in women, on both sides. The thickening fraction did not differ significantly between men and women. In men, it ranged from 60 to 260% on the left side and from 57 to 200% on the right side. In women, it ranged from 58 to 264% on the left side and from 60 to 229% on the right side. The lower limits of normality of the thickening fraction were determined to be 40 and 39% in men and 39 and 48% in women for the right and left hemidiaphragms, respectively. The upper limit for normal of the mean of both sides of the ratio thickness at end-inspiration divided by the thickness at deep breathing was determined to be 0.78 in women and 0.79 in men. Conclusion: The normal values of thickness and the indexes of diaphragmatic function should help clinicians with detecting diaphragm atrophy and dysfunction.